Gender Based Violence and the Law - Klugman, Jeni (World Bank, Washington, DC, 2017)
The phenomenon of gender-based violence is pervasive around the world, experienced by some one in three women in their lifetimes. The elimination of such violence has been increasingly recognized as a priority for the international community. This paper investigates the potential and shortcomings of legislative action – and how international and national laws can interact with norms in ways that can be conducive to the reduction of the risk of violence. We argue that there has been major progress in establishing the right of women to live free of violence in both international and national law, especially over the past decade or so, with civil society movements at the local and global levels playing a pivotal role. At the same time, there is some way to go to address the underlying norms and behaviors associated with violence. The investigation sheds some light on broader debates about the value of international human rights law. Some regard international agreements and conventions as toothless, others point to evidence that these have helped to mobilize women’s groups. One channel of effects could be the following. International laws and norms set out standards of behaviour that are regarded as appropriate by a critical mass of nation-states, and such norms affect domestic policy making along a variety of causal pathways, including standards for domestic legislation, creating standards for global civil society to both advocate and monitor, and mobilizing domestic civil society around these new shared expectations of individual and state behavior. The paper is structured as follows. The outline the significance of gender-based violence, globally and regional and country patterns. This is followed by an examination of the international legal framework. Our review highlights the important role of civil society, and especially women’s groups, both in terms of bringing about reform and monitoring implementation. The focus of this paper is on intimate partner violence directed at women – that is psychological and emotional, as well as physical and sexual violence, inflicted by a spouse, live-in partner or boyfriend.Intimate partner violence comprises the bulk of gender-based violence in all countries around the world.